The secret life of words [videorecording (DVD)] - Coixet, Isabel; Polley, Sarah; Robbins, Tim, 1958-; Cámara, Javier (Universal Studios Home Entertainment, 2007)
Hannah, who wears a hearing aid, is forced to go on holiday. On holiday she finds a job caring for Josef. Josef is a burn victim on an oil rig who temporarily lost his sight. Hannah's job is to care for Josef until he is stable enough to be transferred. There is almost no one on the rig, except a cook, an oceanographer and a few others out at sea. Hannah tends to Josef and he slowly breaks her shell of silence.